Customer knowledge management application in Malaysian mobile service providers - Sulaiman, Shamsuddin; Mohd Ariffin, Mohd Khairol Anuar; Esmaeilian, Gholamreza; Faghihi, K.; Baharudin, B. T. Hang Tuah (Elsevier, 2011)
In this paper, the aim was to examine the essentially of Customer Knowledge Management (CKM) in Malaysia mobile service providers. In addition, how would customers accept CKM would be discussed. The survey respondents were limited to college students from three main university of Malaysia. It is found in the survey that the current system would not fully satisfy clients, and they need a more enhanced knowledge sharing system. Furthermore, respondents showed their potential and ability to share knowledge through CKM desired channels with mobile service providers to get better and enlarged services.